Strategic Contributions of Indonesian Women Scholars in Shaping Contemporary Islamic Education - Munawati, Siti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study explores the influence of the thoughts of three prominent Indonesian women scholars, Prof. Dr. Zakiah Drajat, Prof. Dr. Tutty Alawiyah, and Prof. Dr. Huzaemah Tahido Yanggo, on the development of Islamic education in Indonesia. Specifically, it investigates how their intellectual contributions and leadership have shaped Islamic educational discourse and practices in response to contemporary societal challenges. Using a qualitative descriptive method and literature-based analysis, this research applies deductive reasoning and historical approaches, including heuristic, verification, interpretation, and historiography. Data were collected through observation, document analysis, and literature review. The results demonstrate that these scholars have played significant roles in advancing Islamic education by their respective fields of expertise, strengthening religious institutions, and promoting inclusive Islamic thought. Their contributions reflect strategic efforts to integrate Islamic values with modern educational needs, highlighting their impact as transformative religious leaders.